Проектоване рівняння Гроса–Пітаєвського для бозе-ейнштейнівських конденсатів кільцевої форми - Prikhodko, O.O.; Bidasyuk, Y.M. (Publishing house "Academperiodika", 2021)
We propose an alternative implementation of the projected Gross–Pitaevskki equation adapted for a numerical modeling of the atomic Bose–Einstein condensate trapped in a toroidally shaped potential. We present an accurate efficient scheme to evaluate the required matrix elements and to calculate tthe ime evolution of the matter wave field. We analyze the stability and accuracy of the developed method for equilibrium and nonequilibrium solutions in a ring-shaped trap with an additional barrier potential corresponding to recent experimental realizations.